Zap it track it: the application of Lean Six Sigma methods to improve the screening system of low-grade mucinous neoplasms of the appendix in an acute hospital setting. (28th October 2019) - McGrath, kathleen; Casserly, Mairéad; O'mara, Freda; Mulsow, Jurgen; Shields, Conor; Staunton, Oonagh; Teeling, Seán Paul; Ward, Marie
Abstract: Objective: To improve the number of patients receiving annual computed tomography (CT) scan and tumour markers, who are diagnosed with low-grade mucinous neoplasms (LAMN). Design: A pre-/post-intervention design was employed using Lean Six Sigma methods to identify gaps in the screening system and to develop and implement solutions for a more robust, auditable screening programme. Setting: The patients diagnosed with LAMN of the appendix referred to the acute hospital and are enrolled in the screening service. Participants: Consultant colorectal surgeons, cancer nurse specialist, colorectal medical team and quality improvement staff. Interventions: Diagnostic tools identified gaps in the current process. A set of improvements were implemented to standardize the pathway for referral and surveillance of patients, provide information on the condition and treatment and standardize and track information received by patients and their referring hospital. Main Outcome Measure(s): Pre and post-intervention outcome measures were taken for the number of patients who receive an annual CT of thoracic, abdomen and peritoneum and tumour markers and number of patients who receive information and contact details. Results: At baseline, of the 28 patients that met the inclusion criteria only 61% had a correct follow-up. Following the implementation of improvements, 78% of patients had correct follow-up and 90% had received information. Conclusions: Gaps in the current cancer screening system were identified and improvements implemented a reduced number of patients having an incorrect follow-up. Findings are applicable across all precancerous screening systems irrespective of the type of malignancy. The methods used empowered patients and fostered an interdisciplinary team approach to care.